Comparison of ground reaction forces and contact times between 2 lateral plyometric exercises in professional soccer players - Wong, D. P.; Chaouachi, A.; Dellal, A.; Smith, A. W. (International Journal of Sports Medicine, 2012)
There are no studies which have examined the differences in kinetics between lateral plyometric exercises and the selection of these exercises is largely based on the experience and observation of coaches. This study aimed to compare ground reaction forces (GRF) and contact times (GCT) between 2 lateral plyometric exercises: lateral alternative leg hopping (HOP), and speed lateral footwork (SPEED). 16 professional male soccer players (age: 24.6±5.5 years; and BMI: 21.7±2.2 kg.m - 2) participated in this within-participant repeated measures study. 3-dimensional GRF data were measured by force platform. Our study revealed significant differences between the 2 lateral plyometric exercises in all kinetics parameters (F=573.7, P<0.01). HOP produced significantly longer GCT (0.45 s vs. 0.23 s, P<0.01, large effect), significantly higher values (P<0.05, large effect) in peak force (3.31 vs. 2.47 Body Weight [BW]), peak rate of force development (0.94 vs. 0.29 BW/s), and impulse (0.76 vs. 0.31 BW.s) except for peak force in the medial-lateral (P<0.05, medium effect) and impulse in the anterio-posterior direction (not significant, small effect). Therefore, SPEED is an exercise that aims to increase step frequency because of its short GCT (< 0.25 s) while HOP increases leg strength and power.